Clinicopathologic characteristics of HER2-positive pure mucinous carcinoma of the breast - Yunjeong Jang; Hera Jung; Han-Na Kim; Youjeong Seo; Emad Alsharif; Seok Jin Nam; Seok Won Kim; Jeong Eon Lee; Yeon Hee Park; Eun Yoon Cho; Soo Youn Cho (Korean Society of Pathologists & the Korean Society for Cytopathology, 2020)
Background Pure mucinous carcinoma (PMC) is a rare type of breast cancer, estimated to represent 2% of invasive breast cancer. PMC is typically positive for estrogen receptors (ER) and progesterone receptors (PR) and negative for human epidermal growth factor receptor 2 (HER2). The clinicopathologic characteristics of HER2-positive PMC have not been investigated. Methods Pathology archives were searched for PMC diagnosed from January 1999 to April 2018. Clinicopathologic data and microscopic findings were reviewed and compared between HER2-positive PMC and HER2-negative PMC. We also analyzed the differences in disease-free survival (DFS) and overall survival according to clinicopathologic parameters including HER2 status in overall PMC cases. Results There were 21 HER2-positive cases (4.8%) in 438 PMCs. The average tumor size of HER2-positive PMC was 32.21 mm (± 26.55). Lymph node metastasis was present in seven cases. Compared to HER2-negative PMC, HER2-positive PMC presented with a more advanced T category (p < .001), more frequent lymph node metastasis (p = .009), and a higher nuclear and histologic grade (p < .001). Microscopically, signet ring cells were frequently observed in HER2-positive PMC (p < .001), whereas a micropapillary pattern was more frequent in HER2-negative PMC (p = .012). HER2-positive PMC was more frequently negative for ER (33.3% vs. 1.2%) and PR (28.6% vs. 7.2%) than HER2-negative PMC and showed a high Ki-67 labeling index. During follow-up, distant metastasis and recurrence developed in three HER2-positive PMC patients. Multivariate analysis revealed that only HER2-positivity and lymph node status were significantly associated with DFS. Conclusions Our results suggest that HER2-positive PMC is a more aggressive subgroup of PMC. HER2 positivity should be considered for adequate management of PMC.